Micro-field of Verbal Plurality in Latin - Bohdan Cherniukh (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The presented research deals with one of the components of the functional-semantic field of aspectuality namely the microfield of verbal plurality.